ICE manual of construction materials : metals and alloys - Sha, Wei.; Institution of Civil Engineers (Great Britain). (London : Thomas Telford, 2010)
'ICE manual of construction materials is an invaluable resource for practising civil and structural engineers in consulting firms, government agencies, research institutes, universities and colleges. Its highly practical approach will guide and train readers towards achieving expertise in the use of major and emerging construction materials. Section 5 of the two-volume manual, Metals and alloys covers: the nature and behaviour of alloys; ferrous metals; aluminium, copper; zinc; titanium; and structural steel. Key features of the manual includes case studies, common problems and practical advice.'--Publisher's description.
These chapters originally published in the 2 v. ICE manual of construction materials.
Includes bibliographical references and index.
Keywords: Metals -- Handbooks, manuals, etc; Alloys -- Handbooks, manuals, etc; Building materials -- Handbooks, manuals, etc